2021
DOI: 10.3390/ani11102775
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Provides Insights into Hepatic Responses to Trichloroisocyanuric Acid Exposure in Goldfish (Carassius auratus)

Abstract: In this study, goldfish (Carassius auratus) were exposed to 0 (control group) and 0.81 mg/L TCCA for four consecutive days. The liver transcriptome, the molecular indices of oxidative stress, and gills histopathology were investigated. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated that energy metabolism-related pathways such as glycolysis/gluconeogenesis were significantly enriched, suggesting their perturbation in the liver of goldfish. Additionally, TCCA exposure also caused pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Interestingly, recent developments related to TCIC suggest that it may have damaging effects. In a recent study, using goldfish as a model, Zhou et al (6) have shown that TCIC exposure for 4 days not only caused oxidative damage by increasing the ROS (reactive oxygen species) production and inhibiting antioxidant enzymes in the liver but also induced pathological damage in respiratory organs of goldfish.…”
Section: Commentarymentioning
confidence: 99%
“…Interestingly, recent developments related to TCIC suggest that it may have damaging effects. In a recent study, using goldfish as a model, Zhou et al (6) have shown that TCIC exposure for 4 days not only caused oxidative damage by increasing the ROS (reactive oxygen species) production and inhibiting antioxidant enzymes in the liver but also induced pathological damage in respiratory organs of goldfish.…”
Section: Commentarymentioning
confidence: 99%